Effect of Nano-Cobalt Oxide on the Rheological Behavior of Asphalt Binder and Mechanical Characteristics of Hot Mix Asphalt. (4th January 2023) - Hamedi, Gholam Hossein; Pakenari, Mohammad Mazhari; Tabrizi, Masoud Toghrol; Pirbasti, Zahra Ranjbar
Abstract : In this study, the effects of nano-cobalt oxide (nano-CoO) (1 and 2% by asphalt binder weight) on the rheological behavior of the asphalt binder and mechanical characteristics of asphalt mixtures were examined. To evaluate the behavior of the asphalt binder at moderate and high temperatures, the dynamic shear rheometer (DSR) test was used. Besides, to study asphalt mixtures' rutting potential and fatigue cracking, the repeated load axial (RLA) test and the indirect tensile fatigue test (ITFT) were conducted, respectively. Based on the rheological tests, adding 1 and 2% of nano-CoO to asphalt binder increases the complex modulus ( G ∗ ) and reduces the phase angle ( δ ) at high temperatures and significantly improves the modified asphalt binder's rutting parameter. Also, at moderate temperatures, the addition of nano-CoO reduced the fatigue parameter of the modified asphalt binder compared to the control asphalt binder. It was demonstrated that the permanent strain of the modified specimens was decreased by about 35% compared to that of the control specimens. The fatigue tests at two temperatures and five stress levels also showed that incorporating nano-CoO significantly increased (about 90%) the fatigue life of modified samples compared to controlled samples.